Implementation of IMS Testbeds Using Open Source Platforms - Pavel Segec; Tatiana Kovacikova (Communications - Scientific letters of the University of Zilina, 2012)
The IP Multimedia Subsystem (IMS) is a control architecture framework for the Next Generation Network (NGN). It is expected that this new network architecture will provide a new kind of IP multimedia services delivered in network converged environments. The NGN and IMS, even after the years of a standardization effort, are still hot networking topics. One of the communities, which adopt emerging communications standards into their products fast, is the open source community. In present days, there are a few open source products, which allow building the IMS environment. However, there are at least two domains for which they are especially helpful. It is teaching/learning of the IMS architecture and testing service eployment in a nearly real environment. This article provides a survey of available open source products. It also describes the experience with the implementation, establishment and running an IMS testbed, which has been built up on an open source client and server entities. At the server side, the focus is on the Kamailio IMS platform.